Efeitos de diferentes fontes e concentrações de cromo sobre aspectos metabólicos e desempenho em tilápias do nilo (oreochromis niloticus) - Kassia Amariz Pires (2010)
Many researches that have evaluated the chromium effect on animals metabolism have showed that chromium is responsible for the intensification on insulin effects and so improve the metabolism of proteins, carbohydrates and lipids. Beyond that, the chromium acts directly or indirectly on blood parameters, such like glucose, cholesterol,triglycerides, proteins and lipoproteins. This experiment has been conducted to evaluate two sources of chrome (chromium yeast and chromium chelate) in terms of performance, carcass composition and fillet, indexes and viscera composition, and blood parameters. The experiment was done in five different levels used in tilapias (Oreochromis niloticus). The rations were formulated to be isoenergic and isoproteic,with a difference only on proportion and type of chromium. The treatments were defined by the chromium source and level, being: T1 = 1,34ppm of chromium yeast; T2 = 2,05ppm of chromium yeast; T3 = 2,8ppm of chromium yeast; T4 = 2,85ppm of chromium yeast; T5 = 2,54ppm of chromium chelate; T6 = 1,91ppm of chromium chelate; T7 = 2,32ppm of chromium chelate; T8 = 2,57ppm; T9 = 0,17ppm no source of chromium, considered the control. The experimental lineation was random, constituted by nine treatments with three repetitions of 12 fish each one. The water parameters have had ideal values for the normal development of the tilapia. There was no statistical differences (P>=0,05) between the levels of the sources tested for the parameters of development (ration consumption, alimentary conversion, weight gain and fillet efficiency), somatic index (liver and spleen weight), carcass and file composition (MS, ashes, EE, PB), blood parameters (glucose, total cholesterol, HDL,LDL, VLDL, triglycerides, total protein) and the values of liver triglycerides. These results suggest that those sources and chromium levels are not sufficient to improve performance and biological functions on tilapia.